2018
DOI: 10.1109/jssc.2017.2787759
|View full text |Cite
|
Sign up to set email alerts
|

Outphasing Class-E Power Amplifiers: From Theory to Back-Off Efficiency Improvement

Abstract: Abstract-This paper presents an analysis of outphasing class-E Power Amplifiers (OEPAs), using load-pull analyses of single class-E PAs. This analysis is subsequently used to rotate and shift power contours and rotate the efficiency contours to improve the efficiency of OEPAs at deep power back-off, to improve the Output Power Dynamic Range (OPDR) and to reduce switch voltage stress. To validate the theory a 65nm CMOS prototype, using a pcb transmission-line based power combiner was implemented. The OEPA provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…For high efficiency at back-off as well as at maximum output power, non-isolating power combiners are required. Non-isolating combiners ensure high efficiency (ideally 100%) by providing optimum impedances both at maximum output power power as well as at a specific power back-off level [3], [4]. Employing non-isolating power combiners, however, results in loadpulling between the two branch PAs that cause input-output phase difference to deviate from ∆θ in = ∆θ out yielding nonlinearity (distortion).…”
Section: Vin Max(vin)mentioning
confidence: 99%
See 4 more Smart Citations
“…For high efficiency at back-off as well as at maximum output power, non-isolating power combiners are required. Non-isolating combiners ensure high efficiency (ideally 100%) by providing optimum impedances both at maximum output power power as well as at a specific power back-off level [3], [4]. Employing non-isolating power combiners, however, results in loadpulling between the two branch PAs that cause input-output phase difference to deviate from ∆θ in = ∆θ out yielding nonlinearity (distortion).…”
Section: Vin Max(vin)mentioning
confidence: 99%
“…In [4] the authors showed that, depending on the class-E PA parameters and on the OEPA branch amplifiers' load trajectories, identical voltage source modeling of switch mode class-E PAs is valid only under specific conditions. Moreover, in this current work, we show that the output impedance of a class-E PA is load-dependent which then necessitates a new theoretical model to describe the linearity performance of outphasing transmitters employing class-E PAs as branch amplifiers.…”
Section: Vin Max(vin)mentioning
confidence: 99%
See 3 more Smart Citations